BIOPHILOSOPHY: METHODOLOGICAL APPROACH AND THE CHALLENGES OF ARTIFICIAL INTELLIGENCE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines biophilosophy as an integrative scientific-philosophical discipline emerging at the intersection of the ontology of life, philosophy of science, and bioethics in the context of digital transformation. The ontological foundations of biophilosophy are grounded in the critique of reductionism, the principles of systemity and emergence, and the recognition of the historicity and processual nature of life. A methodological model is proposed based on dialectical analysis, interdisciplinary synthesis, phenomenological perspective, and normative-ethical reflection. Particular attention is paid to artificial intelligence as an epistemic mediator transforming the language of life sciences and reinforcing tendencies of computational reductionism. The limits of the algorithm are analyzed in relation to historicity, embodiment, and the impossibility of algorithmizing responsibility. The study concludes that biophilosophy is a methodologically autonomous discipline necessary for critically interpreting technological transformations of life in the age of AI
Keywords: biophilosophy, ontology of life, methodology of science, artificial intelligence, algorithmic rationality, computational reductionism, emergence, systemity, embodiment, responsibility, bioethics, limit of the algorithm